Pendidikan Akidah dalam Surah Mu'awwidzatain - Karolina, Asri; Arcanita, Rafia; Sari, Riri Purnama; Idris, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Akidah Education in Surah MuawwidzatainThis research is motivated by the fact that there are still many Muslims who do not fully understand the issue of faith and only follow the culture of their ancestors or customs that have existed since ancient times. The purpose of this study is to analyze the creed education contained in the Surah Mu'awiidzatain. This study uses a type of library researchÂ using a thematic interpretation approach. The method used is the method of